The Implicit Incentive Effects of Horizontal Monitoring and Team Member Dependence on Individual Performance - Sedatole, Karen L.; Swaney, Amy M.; Woods, Alexander (Contemporary Accounting Research, 2016)
Abstract This study examines the implicit incentive effects of horizontal monitoring and team member dependence for individuals working in teams but facing explicit incentives based solely on measures of individual performance. We combine proprietary performance data with survey data for 133 internal auditors. We show that the social influences of relatively high levels of both horizontal monitoring and team member dependence provide implicit incentives that motivate individual performance, making the provision of team rewards unnecessary to ensure individual and team productivity. We conclude that horizontal monitoring and team member dependence are complementary control mechanisms whose effectiveness helps explain the observed practice of organizing work into teams without explicit team‐based rewards.